Anatomical characterization of PDF‐tri neurons and peptidergic neurons associated with eclosion behavior in Drosophila. Issue 8 (1st March 2018) - Selcho, Mareike; Mühlbauer, Barbara; Hensgen, Ronja; Shiga, Sakiko; Wegener, Christian; Yasuyama, Kouji
Abstract: The peptidergic Pigment‐dispersing factor (PDF)‐Tri neurons are a group of non‐clock neurons that appear transiently around the time of adult ecdysis (=eclosion) in the fruit fly Drosophila melanogaster . This specific developmental pattern points to a function of these neurons in eclosion or other processes that are active around pupal–adult transition. As a first step to understand the role of these neurons, we here characterize the anatomy of the PDF‐Tri neurons. In addition, we describe a further set of peptidergic neurons that have been associated with eclosion behavior, eclosion hormone (EH), and crustacean cardioactive peptide (CCAP) neurons, to single cell level in the pharate adult brain. PDF‐Tri neurons as well as CCAP neurons co‐express a classical transmitter indicated by the occurrence of small clear vesicles in addition to dense‐core vesicles containing the peptides. In the tritocerebrum, gnathal ganglion and the superior protocerebrum PDF‐Tri neurites contain peptidergic varicosities and both pre‐ and postsynaptic sites, suggesting that the PDF‐Tri neurons represent modulatory rather than pure interneurons that connect the subesophageal zone with the superior protocerebrum. The extensive overlap of PDF‐Tri arborizations with neurites of CCAP‐ and EH‐expressing neurons in distinct brain regions provides anatomical evidence for a possible function of the PDF‐Tri neurons in eclosion behavior. Abstract : By light‐ and electron microscopy, we in detail describe the projections of the developmentally transient PDF‐Tri neurons in the pharate fly brain and characterize CCAP‐ and EH‐expressing eclosion‐associated peptidergic cells.